Advancing Non Invasive Multi Omics Biomarkers for Early Diagnosis, Precision Medicine, and Improved Therapeutic Outcomes in Endometriosis Management - Muhammad Ardaris Alhudri; Imelda EB Hutagaol; Ismawati Ismawati (Universitas Pahlawan Tuanku Tambusai, 2026)
Endometriosis is a complex, chronic, and multifactorial gynecological disorder characterized by the presence of endometrial tissue outside the uterine cavity, leading to chronic inflammation, pelvic pain, and infertility. One of the major challenges in diagnosing endometriosis is the delay in detection due to nonspecific symptoms, along with the reliance on invasive laparoscopic procedures as the gold standard for confirmation. This condition highlights the urgent need for the development of safer, faster, and more accurate diagnostic methods through the identification of non-invasive biomarkers. This review aims to examine recent advances in various biomarker approaches, including hormonal, immunological, genetic, proteomic, metabolomic, and microbiome-based aspects, which contribute to the pathogenesis of endometriosis and hold potential as diagnostic tools as well as predictors of therapeutic response. The findings indicate that a multi-omics approach integrating genetic data, metabolite profiles, plasma proteins, and microbiota composition has strong potential to generate biomarker panels with higher sensitivity and specificity. Therefore, the development of multi omics-based biomarkers is expected to support early diagnosis and more personalized therapeutic strategies. This advancement represents a crucial step toward the implementation of precision medicine, ultimately improving patients’ quality of life through more effective and targeted management.